Increasing breast support is associated with altered knee joint stiffness and contributing knee joint biomechanics during treadmill running - Powell, Douglas W.; Fong, Hailey B.; Nelson, Alexis K. (Frontiers in Sports and Active Living, 2023)
Introduction Greater breast support has been associated with improved running performance as measured by oxygen cost and running economy. Several candidate mechanisms have been proposed to underlie breast support-related improvements in running performance including increased knee joint stiffness. Greater knee joint stiffness has been associated with improved running performance (speed and metabolic cost), though the influence of breast support on knee joint stiffness has not been previously investigated. Therefore, the purpose of this study was to investigate the influence of increasing breast support on knee joint stiffness and its constituent components during treadmill running. Methods Thirteen recreational runners performed a 3-min running bout at their preferred running velocity in each of three breast support conditions: bare chested (CON), low support (LOW) and high support (HIGH) sports bras. Three-dimensional kinematics and ground reaction forces were collected simultaneously using a 10-camera motion capture system (240 Hz, Qualisys Inc.) and instrumented treadmill (1,200 Hz, Bertec Inc.). Visual3D (C-Motion Inc.) was used to calculate knee joint excursions, moments, powers and work while custom software (MATLAB) was used to calculate knee joint stiffness and breast displacements during the stance phase of running in each experimental condition. A series of 1 × 3 repeated measures analysis of covariance with post-hoc t-tests was used to evaluate the effect of breast support on knee joint biomechanics during treadmill running. Results Increasing levels of breast support were associated with greater knee joint stiffness (p = 0.002) as a result of smaller knee flexion excursions (p < 0.001). Increases in knee extension power (p = 0.010) were observed with increasing levels of breast support while no differences were observed in knee extension moments (p = 0.202) or work (p = 0.104). Conclusion Greater breast support is associated with increased knee joint stiffness resulting from smaller joint excursions. These findings may provide insight into the biomechanical mechanisms underlying previously reported improvements in running performance including reduced oxygen consumption and greater running economy.